1994
DOI: 10.1007/bf00731212
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the sugar-binding site of pea lectin

Abstract: Comparison of x-ray crystal structures of several legume lectins, co-crystallized with sugar molecules, showed a strong conservation of amino acid residues directly involved in ligand binding. For pea (Pisum sativum) lectin (PSL), these conserved amino acids can be classified into three groups: (I) D81 and N125, present in all legume lectins studied so far; (II) G99 and G216, conserved in almost all legume lectins; and (III) A217 and E218, which are only found in Vicieae lectins and are possibly determinants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…However, an aspartic acid residue which is well conserved in the legume lectins (Asp 118 in RBL, Asp 111 in PSL and Asp 89 in GS4; see Fig. 2) and is essential for the binding of lectins to carbohydrates (Van Eijsden et al 1994;Zhu et al 1996), is replaced by a glutamic acid residue at position 115 in PnLPK. We previously showed that replacement of Asp 118 by glutamic acid resulted in the loss of the hemagglutination activity of RBL (Nishiguchi et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, an aspartic acid residue which is well conserved in the legume lectins (Asp 118 in RBL, Asp 111 in PSL and Asp 89 in GS4; see Fig. 2) and is essential for the binding of lectins to carbohydrates (Van Eijsden et al 1994;Zhu et al 1996), is replaced by a glutamic acid residue at position 115 in PnLPK. We previously showed that replacement of Asp 118 by glutamic acid resulted in the loss of the hemagglutination activity of RBL (Nishiguchi et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of a single hydrogen-bonding or sugar-stacking residue within the lectin site of various legume lectins results in loss of glycan binding. For the lectin from Erythrina corallodendron (ECorL), mutation of the hydrogen-bonding residues Asp 89 or Asn 133 to Ala (44) and mutations in equivalent residues in the Phaseolus vulgaris phytohemagglutinin lectin (45), Pisum sativum lectin (46), and Griffonia simplicifolia lectin II (47) result in a loss of sugar binding. A mannose-specific animal lectin with a role in ER-Golgi trafficking, ERGIC-53, is homologous to the legume lectins, and mutation of the conserved Asn residue also results in the loss of lectin activity (48).…”
Section: Lectin Site Mutants Of Calnexin Retain the Ability To Protecmentioning
confidence: 99%
“…Furthermore, in all complexes of the mannose/glucose-specific lectins with their ligands, the above aspartic acid and the asparagine form hydrogen bonds not with the 3-OH and 4-OH of the ligand, as found for the galactose-specific legume lectins, but with the 4-OH and 6-OH groups instead. In pea lectin, one of these mannose/glucose-specific lectins, the above hydrogen bonds were shown to be essential for ligand binding, since substitution of Asp81 (which corresponds to Asp89 in E. corallodendron lectin) by alanine or asparagine, or of Asn125 (corresponding to Am133 in the lectin) by alanine, resulted in loss of activity, without loss of metal binding (van Eijsden et al, 1994). Furthermore, in PHA-L, the leucoagglutinin of Phuseolus vulgaris, a lectin with specificity for N-acetyllactosamine (complex) type oligosaccharides, changing of the combining site Asnl25 for aspartic acid eliminated activity without affecting binding of calcium (van Eijsden et al, 1992).…”
Section: Physicochemical Properties the 19 Refolded Mutants Generallymentioning
confidence: 99%